Matching and Winning? The Impact of Upper and Middle Managers on Team Performance - Thomas Peeters; Steven Salaga; Matthew Juravich (Tinbergen Institute, 2015)
In this paper we investigate the impact of upper and middle level managers on firm performance by simultaneously estimating manager and match qualities for management pairings in Major League Baseball (MLB). We document the economic significance of managers at both organizational levels and illustrate the importance of accounting for match quality in evaluating manager impact. Our results suggest assortative matching as managerial quality is positively correlated across organizational levels. Higher match quality in a pairing is further associated with higher individual manager qualities and longer joint employment spells. Mismatches in educational attainment are linked to lower match quality.
Keywords: M12; M54; L83; 330; match quality; management; team performance; Major League Baseball